Opposite effects of Activin type 2 receptor ligands on cardiomyocyte proliferation during development and repair - Deepika Dogra (Nature Portfolio, 2017)
Zebrafish can regenerate damaged myocardial tissue but it is unclear how this is regulated. Here, the authors show that two TGF-β family members, Mstnb and Inhbaa, have opposite effects in regeneration, with mstnb overexpression or inhbaa loss-of-function causing cardiac scarring after injury.